The position of the United States on the revolution of February 17, 2011 in Libya Historical study - Ali, Laith Ahmed (The International and Political Journal, 2022)
The Libyan-American relations have been characterized by tension, since Colonel Muammar Gaddafi took authority over in 1969, as a result of curbing American influence in Libya and threatening its oil advantages, his support for international terrorism and his interference in the affairs of neighbouring countries and Africa in general, culminating in a series of direct military clashes since 1973. Until 1989 and Libya's policies have not changed towards America since 2003. After the Libyan Revolution broke out on February 17, 2011, got tension in various US decision-making circles regarding it, as Minister of Foreign Affairs Hillary Clinton, US Ambassador to the United Nations Susan Rice, and Samantha Power, Special Assistant to President Obama, supported the military intervention in Libya, while Robert Gates opposed it. President Obama, stipulated obtaining the support of the United Nations and Arab countries, to perform the military operations against Libya. The American policy towards the February 17, 2011 revolution was based on Obama’s policy, which is cooperation with its allies and partners, not working alone, i.e. obtaining the support of NATO, the League of Arab States and the Council of the Arab States. International security, but its decisive role was in changing the Libyan regime and overthrowing Gaddafi but international law does not permit regime change by the international community.